Pengaruh Pemberian Naringenin terhadap Penghambatan Pertumbuhan Sel Kanker : Literature Review - Haura Khairunnisa (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Cancer is a disease that results from changes in cell function and structure, which leads to abnormal and uncontrolled cell division. These changes can affect gene expression, leading to uncontrolled cell proliferation, invasion, and metastasis to other tissues and organs. An alternative to cancer treatment can be done by administering phytochemical compounds, one of which is naringenin. This study aims to determine the effect of naringenin on the growth of cancer cells. The method used in this study is a literature review of in vitro experimental articles published in the last ten years and obtained the results of 7 articles. The study results showed that naringenin can inhibit the proliferation, migration, and invasion of cancer cells through several mechanisms. In addition, naringenin has been shown to induce apoptosis and alter the morphology of cancer cells. It can be concluded that naringenin has great potential as an alternative therapy for cancer.